Immunolymphoscintigraphy for Metastatic Sentinel Nodes: Test of a Model. (28th April 2011) - Chakera, A. H.; Nielsen, B. S.; Madsen, J.; Romer, J.; Kristjansen, P. E. G.; Buch, I.; Binderup, T.; Ingvar, C.; Nalla, A.; Kjaer, A.; Hesse, B.
Abstract : Aim . To develop a method and obtain proof-of-principle for immunolymphoscintigraphy for identification of metastatic sentinel nodes. Methods . We selected one of four tumour-specific antibodies against human breast cancer and investigated (1), in immune-deficient (nude) mice with xenograft human breast cancer expressing the antigen if specific binding of the intratumorally injected, radioactively labelled, monoclonal antibody could be scintigraphically visualized, and (2) transportation to and retention in regional lymph nodes of the radioactively labelled antibody after subcutaneous injection in healthy rabbits. Results and Conclusion . Our paper suggests the theoretical possibility of a model of dual isotope immuno-lymphoscintigraphy for noninvasive, preoperative, malignant sentinel node imaging.